Polish Ophthalmological Society revised guidelines for the management of retinopathy of prematurity - Gotz-Więckowska, Anna; Bakunowicz-Łazarczyk, Alina; Hautz, Wojciech; Filipek, Erita; Niwald, Anna Maria (Klinika Oczna / Acta Ophthalmologica Polonica, 2020)
According to the consensus of Polish neonatologists and the Pediatric Ophthalmology Section of Polish Ophthalmological Society, screening for retinopathy of prematurity (ROP) should be performed in children born ≤ 33 weeks of gestational age with birth weight ≤ 1800 γ and in premature infants born over 33 weeks and weighing over 1800 γ with respiratory failure, low weight gain and other pathologies connected with prematurity qualified by the neonatologist due to the general condition and high risk of ROP. The recommended time of the first examination is in the 4th week of chronological age. Subsequent examinations should be performed at the intervals depending on the retinal vascularization in periods of one to three weeks. If a child is discharged from the hospital before a complete retinal vascularization, parents/guardians must be informed of the need for timely follow-up check-up ophthalmic visits. In the treatment of ROP, laser photocoagulation of the avascular retina or intravitreal anti-VEGF injections (bevacizumab, ranibizumab, aflibercept) are used. Diode or argon laser therapy remains the method of choice for ROP treatment. Current global guidelines do not specify strict indications for the use of anti-VEGF therapy. Available observations suggest its effectiveness in the treatment of aggressive posterior ROP (APROP). Anti-VEGF therapy can be used in patients in whom photocoagulation is difficult or impossible, e.g. when corneal, lens or vitreous haze occurs, or when pupil dilatation is not possible. Treatment should be performed no later than 72 hours after diagnosis. If retinal detachment occurs despite treatment, it is recommended to perform a vitrectomy in selected cases. Treatment is necessary for ROP type 1, defined as: 1. Any stage of ROP in zone I with plus disease, 2. Stage 3 ROP without plus disease in zone I, 3. Stage 2 or 3 with plus disease in zone II. Treatment for both eyes should be considered when ROP type 1 is present in only one eye.